Lifehack Corporation : Smart Table / Muhammad Azrie Othman ...[et al.] - Othman, Muhammad Azrie; Syed Haidzir, Syed Hilmi Hafiz; Nor Hasan, Mohamad Sufian; Amir Abdullah, Muhammed Syukur; Najdi, Mohdlzdihar (2019)
LIFEHACK CO is a company which focuses on services and rental in Malaysia. Table is one of a modern design among students and household. Differences in type and design make our company looks interesting and suitable to have for any occasion. To make it more attractive and interesting, we decided to give a promotion price which is affordable for those who order more than 100 table. Nowadays, people are busy with their work and lack of time to use their electrical appliances in one time . Normally, for student they want to use their laptop or phone while study. So, with our affordable price smart table can help students to improve their comfort. Easy and simple as that.